Hydrogen Production by Algae Scenedesmus sp. Biomass through Photosynthesis Process - Kiki Rezki Lestari; Fitria Hidayanti; Ucuk Darusalam (International Journal of Science and Society, 2022)
The hydrogen production was studied using Scenedesmus sp. by PHM-S media under anaerobic and photosynthesis process. The Investigated of hydrogen gas using by Natural Gas Analyzer (NGA): HP (Hewlett Packard) 6890 with a molecular sieve 5A (CH4, O2. N2, H2) a thermal conductivity detector is used in a mesh-packed column. The results show highest value of hydrogen production in second experiment. It was obtained because the second experiment had longer for incubation time so the photosynthesis process was took longer then algae could produce more hydrogen gas. Interestingly, the hydrogen does not produce within a certain timeframe. We believe that this was related to the reaction enzymatic in algae that was mostly induced by the oxygen, an inhibitor of the hydrogenate enzyme, was reduced during anaerobic adaptation, resulting in an increase in hydrogen production.